The Interconnections between the Czech Methodological Platform and the Ideas of Modern Ukrainian Literature Studies - Tychinina, Alyona (Pitannâ lìteraturoznavstva, 2020)
The article under studies identifies the methodological ties between modern Czech and Ukrainian literary studies on the example of Ivo Pospišil’s monograph “Methodology and Theory of Literary Slavic Studies and Central Europe” (2015). The methodological platform of the scientist is shown in dynamics: comparative studies, phenomenology, historical poetics, genre studies and areal studies. Areal (spatial) philology becomes the methodological framework and “cognitive tool” in the above work. Within the specific features of the hermeneutic circle, I. Pospišil outlines the methodological principles of Brno areal studies, as well as substantiates the powers of areal methodology. Hence, by means of deduction, he narrows the areas of its application and eventually connects spatial poetics to the analysis of specific texts of modern Czech literature. In this respect, areal studies are consonant with the methodology of the N. Kopystyanska’s scientific school. From the standpoint of literary axiology, I. Pospišil characterizes the literary process of 1960–1970 in the way that coincides with the ideas of D. Zatonsky and T. Hundorova. The interpretation of the tropical nature of allegory and symbol, within the areal issues, resonates with a number of Ukrainian investigations. I. Pospišil’s speculations on the problem of auto-reflection and auto-axiology of creativity is based mainly on the concepts of O. Potebnja, on whose methodological reputation rely the works of most Ukrainian researchers. The phenomenon of Central Europe is regarded in the context of “Central European centrism” and multiculturalism, which conceptually brings the scientific research closer to the American studies by N. Vysotska and T. Denisova. I. Pospišil emphasizes the influence of Central European university traditions of the first half of the XX century on the formation of the Prague Linguistic Circle, as well as on the scientific growth of F. Wallman, S. Vilinsky, R Jacobson and R. Wellek. The concept of the history of Russian literature, proposed by I. Pospišil, leads to the profound analysis of the scientific figure of D. Chyzhevsky, which is being widely studied in Ukraine. It is concluded that the “methodological balance” of Czech and Ukrainian literary criticism is ensured by common “pendulum movements” in the history of the literary process, common theoretical and literary basis (works by O. Potebnja, M. Bakhtin, D. Chyzhevsky, D. Ďurišin), parallel influences of Western European literary criticism, as well as collective conference events and consensual research optics.